2015
DOI: 10.1002/bmc.3482
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐exchange vs reversed‐phase chromatography for separation and determination of basic psychotropic drugs

Abstract: Ion exchange chromatography, an alternative to reversed-phase (RP) chromatography, is described in this paper. We aimed to obtain optimal conditions for the separation of basic drugs because silica-based RP stationary phases show silanol effect and make the analysis of basic analytes hardly possible. The retention, separation selectivity, symmetry of peaks and system efficiency were examined in different eluent systems containing different types of buffers at acidic pH and with the addition of organic modifier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
1
Order By: Relevance
“…The alkaloids are compounds with basic properties, which makes them difficult analytes in chromatographic analysis mainly because of strong interactions between their cationic forms and surface‐active groups. These interactions cause widening of spots, poor separation efficiency, and spot asymmetry . In our case, a strong tailing effect could be observed when the mobile phases consisted of methanol and water and consequently, in order to avoid this problem, the pH of the mobile phase has been adjusted to a value of 9.6 by ammonium solution addition, which plays the role of an ionization suppressor.…”
Section: Methodsmentioning
confidence: 85%
“…The alkaloids are compounds with basic properties, which makes them difficult analytes in chromatographic analysis mainly because of strong interactions between their cationic forms and surface‐active groups. These interactions cause widening of spots, poor separation efficiency, and spot asymmetry . In our case, a strong tailing effect could be observed when the mobile phases consisted of methanol and water and consequently, in order to avoid this problem, the pH of the mobile phase has been adjusted to a value of 9.6 by ammonium solution addition, which plays the role of an ionization suppressor.…”
Section: Methodsmentioning
confidence: 85%
“…Возможным решением этих проблем могут стать ионные жидкости (ИЖ), которые, благодаря своей двойственной природе, позволяют поддерживать ряд важных для хроматографии межмолекулярных взаимодействий как с поверхностью сорбента, так и с аналитами [9], что делает их перспективными добавками в ОФ ВЭЖХ [10]. Анализируя современную литературу можно найти большое количество статей, посвященных применению различных ИЖ в качестве модификатора подвижной фазы при анализе и разделении биологически активных соединений, лекарственных препаратов, белков и даже взрывчатых соединений методом ВЭЖХ [5,6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Использование ИЖ в ОФ ВЭЖХ анализе позволяет регулировать времена удерживания биологически активных соединений при их одновременном содержании в пробе [11], не влияя при этом на порядок выхода соединений [12].…”
Section: Introductionunclassified
“…[19][20][21] When alkaloids are analyzed by HPLC methods, broadening and tailing are the main problems that need to be addressed. [22][23][24] In our previous study, the alkaloids of DLF were achieved by baseline separation, but the peak tailing still inuenced the quantitative determination of alkaloids in DLF. 4 Recently, it was reported that mobile phase additives could be successfully used to solve the problem of broadening and tailing.…”
Section: Introductionmentioning
confidence: 99%